(untitled) (Critical Journal of Social Sciences, 2026)
The study explores the developments of criminal careers of individuals engaged in organized crime in Sri Lanka, where the lens of the research is the application of Differential Association Theory and Rational Choice. Criminal networks continue to develop internationally and locally. This study implements a mixed-methods approach, inclusive of semi-structured interviews with 30 incarcerated offenders and questionnaires with rehabilitation officers. The results of the study established evidence of peer association, initial context of family background and level of deviance as the main influences to initiate participating in an organized crime network and supporting DAT. As offenders build a body of experience and status in the organized crime network, they begin to behave more strategically, consistent with RCT and rationale-based decisions involving risk assessment, opportunities available, and anticipated outcomes. The research also discovers structural barriers low education, unemployment, and social marginalization as long triggers and reinforcing antecedents of sustained crime involvement. Developing a criminal career from social learning to rational choice, this study advances theoretical understandings and offers insights for practice. It also advocates for prevention and rehabilitation interventions appropriate to the offender’s position on the criminal career continuum, especially places like Sri Lanka, where socio-political circumstances intersect with organized crime.